2018
DOI: 10.1080/13813455.2018.1482355
|View full text |Cite
|
Sign up to set email alerts
|

Role of some circulating MiRNAs on breast cancer diagnosis

Abstract: Aberrant expression of miRNAs has a link with tumorgenesis and their deregulation is reported in biological fluids of cancer patients. Authors aimed to investigate the diagnostic role of miRNA-17-5p, miR-155 and miRNA-222 in serum samples from breast cancer patients (n = 80), benign breast patients (n = 40) and healthy individuals (n = 30) using quantitative real-time PCR technique. Median levels of investigated markers revealed significant increase in primary breast cancer followed by benign and control group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 46 publications
0
12
0
2
Order By: Relevance
“…An in-depth analysis of the data suggested that circulating miRNAs were identified as potential diagnostic biomarkers for BC lacked specificity and often showed discordant expression in the blood and tissue of patients affected with cancer. The final processing of our in-depth analysis revealed that a circulating miRNA signature for BC diagnosis is currently unavailable because the most frequently studied circulating miRNA, BC-associated miRNAs (miR-155, miR-21, miR-195, and miR-145), except for miR-195, are the most non-specific BC-associated miRNAs, although some of these miRNAs were able to discriminate patients with BC from patients with benign breast lesions (BBLs) (miR-21 [69,78]; miR-155 [79,80]; miR-145 and miR-195 [61]). Factors triggering neoplastic transformation may differ among tumors, but the common denominator for all neoplastic diseases is uncontrolled cell growth and the activation of inflammatory processes.…”
Section: Discussionmentioning
confidence: 99%
“…An in-depth analysis of the data suggested that circulating miRNAs were identified as potential diagnostic biomarkers for BC lacked specificity and often showed discordant expression in the blood and tissue of patients affected with cancer. The final processing of our in-depth analysis revealed that a circulating miRNA signature for BC diagnosis is currently unavailable because the most frequently studied circulating miRNA, BC-associated miRNAs (miR-155, miR-21, miR-195, and miR-145), except for miR-195, are the most non-specific BC-associated miRNAs, although some of these miRNAs were able to discriminate patients with BC from patients with benign breast lesions (BBLs) (miR-21 [69,78]; miR-155 [79,80]; miR-145 and miR-195 [61]). Factors triggering neoplastic transformation may differ among tumors, but the common denominator for all neoplastic diseases is uncontrolled cell growth and the activation of inflammatory processes.…”
Section: Discussionmentioning
confidence: 99%
“…Several recent studies have demonstrated that miRNAs are stably detectable in plasma/serum [28,29,30]. MiRNA-221 and miRNA-222 are overexpressed in different types of malignant neoplasms including ovarian cancer 31, hepatocellular cancer [32], glioblastomas [33] and breast cancer [10,13,34]. Both miRNAs were shown to promote cell growth, cell cycle progression and invasion in these tumore types in vitro and in vivo [32,33].…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNAs (miRNAs) are a family of highly conserved noncoding single stranded RNA molecules of 21 to 25 nucleotides; It is can regulate one third of protein-coding genes and participate in the developmental and physiological processes of human body [9]. Aberrant expression of miRNAs has a link with breast tumorgenesis and their deregulation is reported in biological fluids of cancer patients [10]. MiRNAs have important regulatory roles in the cell; modulate their target genes through RNA interference pathways (RNAi).…”
Section: Introductionmentioning
confidence: 99%
“…A associação entre pCR e melhora da sobrevida parece estar restrito à alguns subtipos moleculares do câncer de mama (DÍAZ-CASAS et al, 2019;FIROUZABADI et al, 2019;HARBECK;GNANT, 2017). (FERRACIN et al, 2015;LÜ et al, 2017;SWELLAM et al, 2018b;ZHU et al, 2018 HU et al, 2018;LI et al, 2017;MISHRA et al, 2015;YAMADA et al, 2018 direta entre a desregulação dos miRNAs e a progressão tumoral (SWELLAM et al, 2018b;ZHU et al, 2018).…”
Section: Agradecimentosunclassified
“…Os miRNAs regulam inúmeras vias do câncer, promovendo proliferação, invasão e metástase (HU et al, 2018;IWASAKI et al, 2015;LI et al, 2017;SWELLAM et al, 2018b…”
Section: Agradecimentosunclassified